National study of hearing preservation rates and outcomes after cochlear implantation in Ireland. (3rd September 2022) - Gendre, Adrien; Quinn, Sarah; Jones, Holly; Hintze, Justin; Simões-Franklin, Cristina; Walshe, Peter; Viani, Laura; Glynn, Fergal
Abstract : Objective: To study the rate of hearing preservation and outcomes of hearing preservation candidates in a national cochlear implant centre. The HEARRING criteria was used. Methods: All cochlear implant candidates with preserved low frequency pure tone average (PTA) were included. All patients underwent cochlear implantation using a standard 'soft-surgery' technique. PTA was assessed at switch-on, 3, 6, 9 and 12 months postoperatively. The primary outcome was hearing preservation at 12 months. Results: Sixty six patients were included in the study between 2015 and 2020. Seventy one ears were implanted including 33 adults and 33 children with 5 bilateral implantations. Mean preoperative PTA was 74.8 dB (range 52.3–92 dB), mean postoperative PTA was 95.3 dB corresponding to a mean shift of 20.5 dB. In the adult population, HP rates were as follows: complete HP in 13%, partial HP in 39.1%, minimal HP in 30.4%, loss of hearing in 17.4%. In the paediatric population: complete HP in 20.7%, partial HP in 51.7%, minimal HP in 13.8% and loss of hearing in 13.8%. After the initial postoperative shift, there was no significant worsening of residual hearing during follow-up between 3 and 12 months. There were no significant prognostic factors for hearing preservation. Conclusion: Hearing preservation rates using the HEARRING criteria are described. This study will help counselling and decision making in patients eligible for cochlear implantation with hearing preservation. Further studies are required to assess the performances and outcomes of electronatural and electroacoustic stimulation.